Diseño y fabricación de estructura denominada TORRE N°3 para optimizar el mantenimiento al filtro de banda en la CÍA. MINERA MISKIMAYO basado en la NORMA VDI 2221 - Valderrama Pereyra, Mike Bryan (2023)
Our country has important mining projects, in which interesting challenges are faced every day from mineral extraction, production processes to environmental care, it is there where engineering plays a crucial role, providing effective and comprehensive solutions. The present work focuses on providing a solution to a need of a mining company in the north of the country. The company FACTORÍA INDUSTRIAL SAC. Headquartered in the city of Trujillo, it provides a variety of services for companies in the region, among which is one of its most important clients, COMPAÑÍA MINERA MISKIMAYO (with acronym CMMM, as it will be called from this paragraph on). At CMMM they faced a problem that caused breakdowns and unexpected production stoppages, which entailed considerable economic losses. The problem addressed consisted of having a structure with certain characteristics that provides access to the BAND FILTER, which is a priority part in the drying process of the CMMM plant. For which, field visits were made, with the objective of obtaining technical information that the structure must have and also coordinating with personnel from the areas involved. All this information was developed in the engineering area of FISAC Trujillo, developing possible solution designs that meet the requirements that said structure should have. In the design stages, we worked based on some methods provided by the VDI 2221 standard and the national building regulation RNE E.090 for the design and manufacture of metal structures. Design software was also used, including SOLIDWORKS to carry out the analysis of loads that will act on the structure, obtaining maximum effort and deformation results, these values indicate in which areas it was necessary to reinforce the structure, along with that, we worked with a reasonable factor of safety. Finally, the parts, assembly plans and the list of materials of the structure are provided to proceed with the manufacture